Selection of third-party relationships in construction [Selección de Formas de Relación con Terceros en la Construcción] - Palacios Riofrio, J. (2017)
Construction projects involve intensive and constant interaction among the parties involved. This interaction requires an efficient use of collaborative processes focused on the fulfillment of the project's objective. Traditional types of relationships have proven ineffective in developing successful projects, and can generate adverse relationships between the parties negatively influencing performance. Using primarily an exploratory and descriptive approach, the following research has developed a tool to improve the relationships between those involved in the course of a construction project. Based on an extensive literary review in which the principles of Partnering, Alliancing, Lean Project Delivery, and Relational Contracts were analyzed, and considering interviews with project management experts, three types of relationships were identified that can be used to establish contractual relationships: (1) traditional/transactional, which operates on risk transference; (2) partnering/transactional with agreements, which promotes a win-win relationship between parties, supported by good faith and agreements outside the original contract; and (3) alliancing/relational, which uses a formal agreement to align objectives and interests of the parties in mutual benefit for the project. These types of relational/contractual interactions are implemented in an informal matrix that supports the selection of the optimal type of interaction for a determined project. There is also a discussion of the potential consequences of the correct selection of a relationship type so as to improve the project performance and the relationships of the parties involved.